Tamarindus indica fruit: Pharmacognostical standardization, detection of contaminant, and in vitro antioxidant activity - Mohd Amir; Niyaz Ahmad; Md Sarfaroz; Wasim Ahmad; Sayeed Ahmad; Mohd Mujeeb; Faheem Hyder Pottoo (Wolters Kluwer Medknow Publications, 2019)
Objective: The main objective of the current study was to perform pharmacognostical, physiochemical analysis and in vitro antioxidant activity of Tamarindus indica Linn. (Family: Fabaceae) fruit. Materials and Methods: The present study deals with pharmacognostical characters as identification parameters of the fruit, which were subjected to macro- and microscopical studies. Physiochemical analysis was performed as per World Health Organization-recommended parameters. Toxicological parameters such as heavy metals, aflatoxins, and pesticide residue and presence of microbial count were analyzed. This study also deals with the thin layer chromatography/high performance thin layer chromatography fingerprinting and antioxidant activity. Results: The microscopy study revealed the presence of epidermis, vascular bundles, parenchyma cells, mucilage fiber, starch grain, and nonlignified fibers. Physiochemical parameters such as loss on drying, moisture content, ash value, and extractive value were also determined. Heavy metal, aflatoxin, total microbial load, and pesticide residues were found to be variable but under the permissible limits. Conclusion: It is critical to analyze these parameters in each crude herbal drug before further processing to ensure their safety and efficacy for better approval at the international podium. This study revealed precise identification for the meticulous crude drug which will be valuable in detection and manage to adulterations of the raw material.